Subprodutos da indústria de celulose como corretivos de acidez do solo e fonte de nutrientes na rúcula (eruca sativa mill.) - Daudt, Géssica Ferreira (2015)
Worldwide, Brazil is the fourth largest producer of cellulose. In the industrial processing of cellulose, there remains, which are not incorporated into the final product, termed waste. The waste from the cellulose and paper industry have shown up as a good nutrient source option and corrective ground by presenting low cost and potential for improvement when incorporated into the soil. The objective of the present work evaluate the changes in soil chemical properties, in two soils with different textural classes, corrected with the use of alkaline by-products of the cellulose and paper industry in the cultivation of arugula. The study was conducted at the experimental farm of the Federal University of Espirito Santo in the city of São Mateus-ES. The studied materials were extracted residues of cellulose and paper: with seven gray levels of calcium magnesium - CCM (Biomass ash; Dregs & Grits; mud Cal and Magnesita) and seven levels of Humuativo. Doses of CCM and Humuativo were combined according to the matrix model Box Berard increased 3 (2k + 2K + 2k + 1) constituting 13 treatments over a course of dolomitic limestone, arranged in a completely randomized design (CRD), with three replications. The central point of the matrix (0,0) taken as the standard dose, and referring to 100% of lime requirement for MCC and 25 t ha-1 for Humuativo. The application of the by-products increased pH, exchangeable Ca, Mg, P and V in both evaluated soils and reducing the contents of Al and H + Al. The use of by-products increases the levels of Na + in soil up to 15 times xi the initial value. The waste had studied in their Cu and Ni composition in toxic amounts to plants, preventing their use to address safety in consumption of arugula. The arugula plants had gained momentum when grown in oxisoil. The fresh and dry weight of part of the roots were higher when grown in Ultisol media texture. So much for the Oxisol as to Udult is not recommended dose below 1.34 t ha -1 CCM product.